Digitalizing Menstrual Fiqh Education: The Use of RIMA Application to Support Haid Cycle Monitoring among Female Islamic Boarding School Administrators - Anis Khumaeni; Fitri Andiyani; Putri Lia Ningsih; Widya Sifa; Muhammad Farhan; Ratoni Ratoni (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study explores the use of the RIMA application as a digital learning medium to support menstrual fiqh education among female administrators of Al Ishlah Assalafiyah Islamic Boarding School, Luwungragi. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that the RIMA application contributes significantly to improving participants’ understanding of menstruation-related fiqh, particularly in distinguishing between haid, istihadhah, and periods of purity. The application also facilitates systematic menstrual cycle monitoring, enabling users to connect personal biological experiences with Islamic legal principles. Furthermore, the integration of menstrual data into learning activities promotes experiential and student-centered learning, resulting in greater engagement and critical reflection. Although challenges related to digital literacy and technological adaptation were identified, the study demonstrates that digital tools can enhance the effectiveness of Islamic learning. The findings highlight the potential of RIMA as an innovative model for digitalizing women’s fiqh education in Islamic boarding schools